Corporate Carbon and Financial Performance: A Meta‐analysis. (9th June 2017) - Busch, Timo; Lewandowski, Stefan
Summary: We use meta‐analytical techniques to address the question" When does it pay to be green?" Existing meta‐studies in this research field cover a range of ecological issues and synthesize a variety of environmental performance measurements. This precludes a detailed examination of how differences in measurement approaches account for variations in empirical results. In order to conduct such an examination, we focus on only one ecological issue, climate change, and one particular operational performance dimension: corporate carbon performance as expressed by a firm's level of carbon dioxide (CO2 ) emission equivalents. Our sample comprises 68 estimations from 32 empirical studies, covering a total of 101, 775 observations. In addition to our examination of the causal relationship, we analyze whether differences in operationalizations of carbon performance and financial performance predetermine empirical outcomes. The meta‐analytic findings indicate that carbon emissions vary inversely with financial performance, indicating that good carbon performance is generally positively related to superior financial performance. The results show that relative emissions are more likely to produce statistically significant results than absolute emissions. Furthermore, market‐based measures of financial performance are more positively related to carbon performance than accounting‐based measures. We conclude that measurement characteristics, which were not analyzed in detail by previous meta‐studies, may present a great source of cross‐study variability.